Digitization of and online access to data from the natural history collections of Adam Mickiewicz University in Poznań: Assumptions and implementation of the AMUNATCOLL project - Jackowiak, Bogdan; Błoszyk, Jerzy; Dylewska, Magdalena; Nowak, Maciej M.; Szkudlarz, Piotr; Lawenda, Marcin; Meyer, Norbert (Biodiversity: Research and Conservation, 2022)
This paper describes a project aimed at digitizing and openly sharing the natural history collections (AMUNATCOLL) of the Faculty of Biology at Adam Mickiewicz University in Poznań (Poland). The result of this project is a database (including 2.2 million records) of plant, fungal and animal specimens, which is available online via the AMUNATCOLL portal and on the Global Biodiversity Information Facility website. This article presents selected aspects of the “life cycle” of this project, with a particular focus on its preparatory phase.